2019
DOI: 10.4108/eai.13-7-2018.161419
|View full text |Cite
|
Sign up to set email alerts
|

A review of youth mental health promotion apps towards their fit with youth media preferences

Abstract: INTRODUCTION:Mental health promotion apps can promote youth mental health but fail to engage young people. Fit to young people's media preferences is known to mediate engagement. OBJECTIVES:To explore the fit of existing youth mental health apps with young people's media preferences. METHODS:A workshop with 60 youth psychologists elicits designs of digital mental health interventions. A review of 29 youth mental health apps unpacks their modality strategies. We then compare modality strategies from literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The shortcomings of PPIs with regard to individual preferences and modalities line up with the aforementioned study on PP apps for young people [20], which showed an overreliance on static text and writing and a lack of customization for young people to shape interventions according to their own preferences and strengths, in contrast to what young people expect from digital instantiations [19]. The researchers attributed these issues to technology design, saying that "the design of these technologies needs to be more closely oriented to what young people are actually interested in" [20]. Although we do not disagree with this assessment, our study indicates that the issue is rooted in a deeper level.…”
Section: Faithfully Translating Ppis For Digital Platformsmentioning
confidence: 77%
See 3 more Smart Citations
“…The shortcomings of PPIs with regard to individual preferences and modalities line up with the aforementioned study on PP apps for young people [20], which showed an overreliance on static text and writing and a lack of customization for young people to shape interventions according to their own preferences and strengths, in contrast to what young people expect from digital instantiations [19]. The researchers attributed these issues to technology design, saying that "the design of these technologies needs to be more closely oriented to what young people are actually interested in" [20]. Although we do not disagree with this assessment, our study indicates that the issue is rooted in a deeper level.…”
Section: Faithfully Translating Ppis For Digital Platformsmentioning
confidence: 77%
“…The Person-Activity Fit (PAF) model describes how the overlap between person features, such as preferences and strengths, and intervention features, such as dosage and variety, impact how well a PPI is performed, which in turn impacts the subsequent well-being increase [13]. Both previous research on digital instantiations of PPI principles for young people [20] and our research presented in this paper suggest that PAF between young people and PPI principles may be overall low, at least with regard to how PPI are currently being delivered, in both digital and analog formats.…”
Section: Faithfully Translating Ppis For Digital Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lead author, who is well versed in the mental health interventions recommended for UMY, selected the apps by: (1) getting an overview of available mental health apps and the list of apps recommended by Michel et al [56]; (2) generating a list of potential apps that focuses specifcally on sleeping problems and stress [33,46] and promoting techniques that are recommended for UMY (e.g., managing worries, mindfulness exercises and sleep hygiene techniques) [46]; and (3) screening the apps according to interaction criteria recommended for maintaining youth engagement (primarily, ofering multi-model input and output [56]) and their Google Play Store/Apple App Store rating. This resulted in four apps being selected to be used in the workshop as described in Table 2.…”
Section: Selection Of Workhop Materialsmentioning
confidence: 99%